Resistance to the Current The Dialectics of Hacking - Söderberg, Johan (Information Policy, 2022)
How hacking cultures drive contemporary capitalism and the future of innovation. In Resistance to the Current, Johan Söderberg and Maxigas examine four historical case studies of hacker movements and their roles in shaping the twenty-first-century's network society. Based on decades of field work and analysis, this intervention into current debates situates an exploding variety of hacking practices within the contradictions of capitalism. Depoliticized accounts of computing cultures and collaborative production miss their core driver, write Söderberg and Maxigas: the articulation of critique and its recuperation into innovations. Drawing on accounts of building, developing, and running community wireless networks, 3D printers, hackerspaces, and chat protocols, the authors develop a theoretical framework of critique and recuperation to examine how hackers-who have long held a reputation for being underground rebels-transform their outputs from communal, underground experiments to commercial products that benefit the state and capital. This framework allows a dialectical understanding of contemporary social conflicts around technology and innovation. Hackers' critiques of contemporary norms spur innovation, while recuperation turns these innovations into commodified products and services. Recuperation threatens the autonomy of hacker collectives, harnessing their outputs for the benefit of a capitalist system. With significant practical implications, this sophisticated multidisciplinary account of technology-oriented movements that seek to challenge capitalism will appeal to science and technology readers interested in innovation studies, user studies, cultural studies, and media and communications.